Community capacity building based on local wisdom through the management of the Brontokusuman tourism village, Yogyakarta - Ratika Tulus Wahyuhana; Endah Tisnawati; Jeki Trimarstuti (Community Empowerment, 2021)
Cultural values must be strengthened as part of local wisdom by increasing community capacity in the management and innovation of tourist attractions. Cultural activities in Dewa Bronto Tourism Village have been running for some time, but their management is still subpar. The community does strongly support tourism activities, but community participation in managing the potential of tourist villages remains low. This service activity aims to increase community involvement in managing the cultural event of Dewa Bronto Tourism Village in Brontokusuman Village through an empowerment approach. Mentoring activities are carried out at various stages of socialization, tourism village management training, tourism product management, and marketing the potential of tourist villages. Implementing community service activities has the potential to increase knowledge, community skills, and form awareness and independence in the management of tourist villages, particularly cultural events. Implementing the program has the potential to increase knowledge, community skills, and form awareness and independence in the management of tourist villages, particularly cultural events. This is demonstrated by the community's active participation in organizing cultural events on its own. Furthermore, the community participated in cultural-themed tourism competitions at the Yogyakarta City level.